2023
DOI: 10.1111/1556-4029.15235
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the effect of heat exposure on hair colored by permanent and semipermanent colorants using surface‐enhanced Raman spectroscopy

Abstract: Confirmatory identification of hair colorants can be used to establish a connection between a suspect and the crime science or demonstrate the absence of such connections. A growing body of evidence shows that surface‐enhanced Raman spectroscopy (SERS) could be a confirmatory, minimally destructive, and fully noninvasive analysis of hair colorants. In SERS, a signal that provide the information about the chemical structure of both permanent and semipermanent dyes present on hair is enhanced by a million‐fold u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Kurouski's group previously used SERS to identify colorants on hair that could not be directly detected using RS [34][35][36][37][38]. Furthermore, SERS is broadly used to detect explosives [39,40], illicit drugs such as heroin and cocaine [41], as well as body fluids [42]. Our group showed that SERS could be used to detect and identify artificial colorants on hair [34,43].…”
Section: Introductionmentioning
confidence: 88%
“…Kurouski's group previously used SERS to identify colorants on hair that could not be directly detected using RS [34][35][36][37][38]. Furthermore, SERS is broadly used to detect explosives [39,40], illicit drugs such as heroin and cocaine [41], as well as body fluids [42]. Our group showed that SERS could be used to detect and identify artificial colorants on hair [34,43].…”
Section: Introductionmentioning
confidence: 88%